ҚАРАМАЛЛАР СҮТИНИҢ БИОСИНТЕЗЛЕНИЎИ ҲӘМ ФИЗИКА-ХИМИЯЛЫҚ ҚӘСИЙЕТЛЕРИ - Алламуратов, Б.; Алламуратова, З.; Есемуратов, П. (FAN va JAMIYAT, 2016)
The article deals with the study of activity of bacteria in the stomach and formation of protein, biosynthesis of amino acids in the stomach of large horned cattle.